2012
DOI: 10.1016/j.ahj.2011.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Perceived sexual difficulties and associated factors in patients with heart failure

Abstract: Background Sexual dysfunction is a common problem of increasing incidence in patients with heart failure (HF). However, there is no knowledge on which demographic, clinical, and quality of life (QoL) aspects are related to difficulties in sexual activity nor on the course of sexual difficulties in patients with HF. less thanbrgreater than less thanbrgreater thanMethods Data on sexual difficulties were collected at 1 and 18 months after an HF hospitalization (n = 792, mean age 69 +/- 12 years, 35% female, mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 26 publications
1
45
0
4
Order By: Relevance
“…This limited implementation of sexual counseling in practice may rightfully be called a concern, because a considerable number of HF patients experience sexual difficulties which have a negative effect on their own quality of life and that of their partners. 6,17 Patients worry about resuming sexual activity and are in need of education and counseling on the topic of sexual health. 1,2 Furthermore, previous research has shown that patients also experience barriers to initiating this topic.…”
Section: Discussionmentioning
confidence: 99%
“…This limited implementation of sexual counseling in practice may rightfully be called a concern, because a considerable number of HF patients experience sexual difficulties which have a negative effect on their own quality of life and that of their partners. 6,17 Patients worry about resuming sexual activity and are in need of education and counseling on the topic of sexual health. 1,2 Furthermore, previous research has shown that patients also experience barriers to initiating this topic.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with HF may report a decrease in sexual performance, a loss of sexual pleasure or satisfaction, a decrease of sexual interest, and a decrease in the frequency of sex 1, 2, 3, 4. For a lot of HF patients, sexual health is important, with 52% of the men and 38% of the women with HF reporting that sex was important and sexual health was impacting their quality of life 5, 6…”
Section: Introductionmentioning
confidence: 99%
“…21,23 Symptoms in patients with HF can disappear spontaneously or return, but if they continue over time they can cause a feeling of distress and trigger hospitalization. [21][22][23] Health-related quality of life is described as being poor in patients with HF. 77,78 Greater number of symptoms in patients with HF has been found to be associated with the decrease in quality of life.…”
Section: -74mentioning
confidence: 99%
“…Patients in the group with high thirst intensity did not have higher thirst distress at the baseline compared to those with low thirst intensity (21 [12][13][14][15][16][17][18][19][20][21][22][23] an outpatient clinic at baseline and the study end (III) and in patients at hospital admission, at discharge, two and four weeks after discharge (IV). …”
Section: Thirst Distressmentioning
confidence: 99%
See 1 more Smart Citation